THE LATITE TYPE OF LATE COLLISIONAL GRANITOIDS (NORTHERN CAUCASUS): GEOCHEMICAL AND MINERALOGICAL FEATURES - Sazonova L.V.; Dokuchaev A.Ya.; Nosova A.A.; Gurbanov A.G. (My University, 2003)
Using ICP-MS technique, investigated are granitoids of Caucasus Mineralnye Vody (GCMV) present in Miocene-Holocene volcanism development area, as well as composition of their mineral components (using EM and electron probing methods). GCMV composition fields are presented. The calculated high degree of enrichment with fluorine confirms belonging of GCMV to high-potassium rocks of late orogenic periods of folded series development. Geochemical characteristics of rocks, minerals' parageneses and composition indicate GCMV belonging to the latite type, whose final differentiation product may be lithium-fluorine granites.